(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article reviews the safety of business functioning in Ukraine. The statistical data on the number of subjects of entrepreneurship by size and the results of their activity are analyzed. Small and medium-sized enterprises, which take up 99,9 % of the total number of business entities, are recognized as the strategic group in the country’s business structure. In order to identify the causes of internal and external threats to the functioning of domestic enterprises, Ukraine’s place in world economic ratings has been considered. According to the results of the study, it is determined that Ukraine is significantly behind in its economic development and compared to neighbouring countries it has an unfavorable business climate for business development. Whereas ratings demonstrate mostly positive dynamics, the level of achievements remains extremely low. According to certain criteria, for example, in the Doing Business rating Ukraine has risen from the 152nd position in 2012 to the 80th position in 2017 ranking. However, there are still a lot of threats and difficulties of doing business that shape the business climate. The external threats and difficulties faced by business entities include: the complexity and opacity of approval procedures and obtaining permits; corruption in licensing, obtaining permits, inspections, customs procedures, tenders, etc.; high tax pressure and instability of tax legislation; devaluation of hryvnia; increased prices for basic energy resources; low investment attractiveness of individual regions and the country as a whole; limited access to funding; instability of the banking sector of the country; insufficient level of property and corporate rights protection, asset-grabbing. The internal threats of entrepreneurship development are: insufficient level of innovation activities; power-consuming production; low labor productivity; ineffective corporate governance; limited information and skills of using modern business financing methods; low financial literacy. Strategic directions for increasing the safety of business operations are identified as follows: elimination or reduction of external threats through effective reforms of the state economic policy; improving the management efficiency at the micro level to overcome the identified internal threats hampering development